Utilization of Economic Rights in Music and Song Works as A Pillar of Creative Economy - Dwi Surya Hartati; Nely Herlina (Faculty of Law, Jambi University, 2018)
The work of songs and music is one of several types of artistic works that is protected by the Act of Copyright. Copyright is regulated through Act No. 28 of 2014 About Copyright (Undang-Undang Hak Cipta or UUHC). Creators and Copyright holders have an exclusive right in the form of economic rights and moral rights. Economic rights can be acquired through the payment of royalty. According to the Act of Copyright, the National Collective Management Institution (Lembaga Manajemen Kolektif Nasional or LMKN) is the institution appointed to collect royalties from creators and/or holders of related rights. LMKN is a non-profit legal entity which has been given an authority by Copyright holders and/or holders of related rights to manage the economic rights in legally collecting and distributing royalties. In order to acquire their share in the royalty, each of the creators, Copyright holders, or the holders of related rights has to become a member of LMKN, and in return said LMKN got the authority to collect royalties from users of said artistic works. Royalty is a form of payment or rewards given to creators and/or Copyrights holders over the utilization of economic rights or related rights of a creation or a product. In Indonesia, there are a lot of LMKNs, in which the function is to collect royalties, including collecting exclusive rights of the holders of related rights. The resulting performance of Collective Management Institutions (Lembaga Manajemen Kolektif or LMK) has not reached its optimum capability for both creators and holders of related rights. The resulting advice of this paper is for the government to create a strict payment system and a method which can also be accessed digitally by the creators.